Sapphism on screen : lesbian desire in French and Francophone cinema - Cairns, Lucille, 1963- (Edinburgh : Edinburgh University Press, 2006)
This book sets out to investigate and theorise mediations of lesbian desire in a substantial corpus of films (spanning the period 1936-2002) by male and female directors working in France and also in French-speaking parts of Belgium, Canada, Switzerland and Africa. The corpus is unique in never before having been assembled, and represents a valuable tool not just for researchers but also for university teachers creating courses both on lesbianism in film and on sexuality in French cinema. A fair number of the 89 texts treated are mainstream films which have achieved high critical acclaim and/or high viewing figures: to cite just a few examples, Henri-Georges Clouzot's Quai des orfÃ·vres (1947), Louis Malle's Milou en mai (1989), Claude Chabrol's La CÃ♭rÃ♭monie (1995), AndrÃ♭ TÃ♭chinÃ♭'s Les Voleurs (1995), and FranÃʹois Ozon's Huit femmes (2001). As such, they have contributed to hegemonic constructions of and debate on (female) homosexuality, in a century wherein sexed/ gendered identity, including sexual orientation, has become a preeminent factor in the constitution of subjectivity. While such constructions and debate have a French-language specificity, and have been produced in distinct socio-political and cultural contexts, this study also engages in analytical comparisons with relevant anglophone films and their own distinct discursive contexts.
Lesbian desire in film: coming to terms -- Bad girls: criminality -- Mad girls: pathology -- Girls on the edge: liminality -- Girls on top: sapphology -- Conclusion.
Filmography: pages 198-209.
Includes bibliographical references (pages 210-214) and index.
Print version record.
JSTOR
Keywords: Homosexuality in motion pictures; Lesbianism in motion pictures; Motion pictures -- France; Motion pictures -- Social aspects -- France; Motion pictures -- French-speaking countries; Motion pictures -- Social aspects -- French-speaking countries; Homosexualité au cinéma.; Lesbianisme au cinéma.; Cinéma -- France; Cinéma -- Aspect social -- France; Cinéma -- Aspect social -- Francophonie; Cinéma -- Francophonie; PERFORMING ARTS -- Film & Video -- Reference; PERFORMING ARTS -- Film & Video -- History & Criticism; Homosexuality in motion pictures; Lesbianism in motion pictures; Motion pictures; Motion pictures -- Social aspects; France; French-speaking countries; Filmkunst; Films; Lesbische liefde